Evaluating the role of selection in the evolution of mitochondrial genomes of aboriginal peoples of Siberia - B. A. Malyarchuk; M. V. Derenko (Вавиловский журнал генетики и селекции)
Studies of the nature of mitochondrial DNA (mtDNA) variability in human populations have shown that proteincoding genes are under negative (purifying) selection, since their mutation spectra are characterized by a pro nounced predominance of synonymous substitutions over nonsynonymous ones (Ka/Ks < 1). Meanwhile, a number of studies have shown that the adaptation of populations to various environmental conditions may be accompanied by a relaxation of negative selection in some mtDNA genes. For example, it was previously found that in Arctic populations, negative selection is relaxed in the mitochondrial ATP6 gene, which encodes one of the subunits of ATP synthase. In this work, we performed a Ka/Ks analysis of mitochondrial genes in large samples of three regional population groups in Eurasia: Siberia (N = 803), Western Asia/Transcaucasia (N = 753), and Eastern Europe (N = 707). The main goal of this work is to search for traces of adaptive evolution in the mtDNA genes of aboriginal peoples of Siberia represented by populations of the north (Koryaks, Evens) and the south of Siberia and the adjacent territory of Northeast China (Buryats, Barghuts, Khamnigans). Using standard Ka/Ks analysis, it was found that all mtDNA genes in all studied regional population groups are subject to negative selection. The highest Ka/Ks values in different regional samples were found in almost the same set of genes encoding subunits of ATP synthase (ATP6, ATP8), NADH dehydrogenase complex (ND1, ND2, ND3), and cytochrome bc1 complex (CYB). The highest Ka/Ks value, indicating a relaxation of negative selection, was found in the ATP6 gene in the Siberian group. The results of the analysis performed using the FUBAR method (HyPhy software package) and aimed at searching for mtDNA codons under the influence of selection also showed the predominance of negative selection over positive selection in all population groups. In Siberian populations, nucleotide sites that are under positive selection and associated with mtDNA haplogroups were registered not in the north (which is expected under the assumption of adaptive evolution of mtDNA), but in the south of Siberia.